Total vs hemi-aortic arch transposition for hybrid aortic arch repair - Kotelis, Drosos; Geisbüsch, Philipp; Attigah, Nicolas; Hinz, Ulf; Hyhlik-Dürr, Alexander; Böckler, Dittmar (Journal of vascular surgery, 2011)
Objective - To compare the outcomes of total aortic arch transposition (TAAT) vs hemi-aortic arch transposition (HAAT) for hybrid aortic arch repair. - Methods - A systematic search was performed using PubMed between November 1998 and May 2010 by two independent observers. Studies included reporting on patients treated by TAAT or HAAT and stent grafting in a proximal landing zone 0 or 1 by Ishimaru, respectively. Further articles were identified by following MEDLINE links, by cross-referencing from the reference lists, and by following citations for these studies. Case reports and case series of less than five patients were excluded. Primary technical and initial clinical success, perioperative, and late morbidity and mortality were extracted per study and were meta-analyzed. - Results - Fourteen studies were included in the statistical analysis. The number of reported patients totaled 130 for TAAT/zone 0 and 131 for HAAT/zone 1. The primary technical success rate was significantly higher in zone 0 than 1 (95% vs 83%; odds ratio [OR], 4.0; 95% confidence interval [CI], 1.47-10.88; P = .0069), due to significantly higher primary type I or III endoleak rates in zone 1 (15.48% vs 3.97%; P = .0050). Reintervention rates were significantly higher in zone 1 (25.81% vs 12.00%; P = .0321). Initial clinical success rates were comparable between zone 0 and 1 (88% vs 85%; OR, 1.35; 95% CI, 0.61-3.02; P = .5354). In-hospital mortality was higher in zone 0 than 1 (8.46% vs 4.58%; P = .2212). - Conclusion - The more invasive TAAT allows a better landing zone at the cost of higher perioperative mortality, therefore, patient selection is crucial.
Gesehen am 07.07.2022